Prevalence of non-communicable diseases and its risk factors among Ijegun-Isheri Osun residents in Lagos State, Nigeria: a community based cross-sectional study - Israel Oluwaseyidayo Idris; Ayodipupo Sikiru Oguntade; Ekow Adom Mensah; Noriko Kitamura (BMC, 2020)
Abstract Background The rapid epidemiologic transition of diseases has adverse implications for low-and middle-income countries (LMICs) like Nigeria due to their limited healthcare, weaker health systems and the westernization of lifestyle. There is a need to evaluate the enormity or otherwise of non-communicable diseases (NCDs) burden in such low resource settings. We performed this survey to determine the prevalence of NCDs and its risk factors among the Ijegun- Isheri Osun community residents of Lagos, Nigeria. Methods A community-based cross-sectional survey was performed on 215 respondents recruited consecutively during a population preventive health campaign. Prevalence of three NCDs (hypertension, diabetes and dyslipidaemia) were calculated. Associations between each of these NCDs and selected risk factors were determined using chi square test. Multivariable logistic regression was used to estimate the risk factors of each of the three NCDs. Results The prevalence of hypertension was 35.3% (95% CI 29.0-42.1), diabetes 4.6% (95% CI 2.2-8.4) and dyslipidaemia 47.1% (95% CI 41.1-54.8). Among the NCD risk factors, the prevalence of smoking was 41.3% (95% CI 34.2-48.6), alcohol consumption 72.5% (95% CI 65.5-78.7), and physical activity 52.9 (95% CI 45.5-60.2). The independent significant predictors of hypertension were age ≥ 60 years (aOR 4.56; 95% CI: 1.72-12.09) and dyslipidaemia (aOR 5.01; 95% CI: 2.26-11.13). Age ≥ 60 years (aOR 8.83; 95% CI: 1.88-41.55) was an independent predictor of diabetes. Age ≥ 60 years (aOR 29.32; 95% CI: 4.78-179.84), being employed (aOR 11.12; 95% CI: 3.10-39.92), smoking (aOR 2.34; 95% CI: 1.03-5.33) and physical activity (aOR 0.34; 95% CI: 0.15-0.76) were independent predictors of having dyslipidaemia. Conclusions The prevalence of hypertension, diabetes and dyslipidaemia and their associated risk factors are high among the respondents of Ijegun-Isheri Osun community of Lagos state, Nigeria. This highlights the need for further implementation research and policy directions to tackle NCD burden in urban communities in Nigeria. These strategies must be community specific, prioritizing the various risk factors and addressing them accordingly.